Evaluasi Pengelolaan Wisata Bahari Pantai Ngliyep Menggunakan Pendekatan Matriks SWOT - Weningingtyas Alindri; Mas Roro Lilik Ekowanti; Ninis Trisyani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Indonesia has a wealth of tourism potential, and Ngliyep Beach in Malang Regency is one example. This stunning beach attracts visitors with its white sand, dense jungle and stunning views. Even though its potential is extraordinary, the number of tourists at Ngliyep Beach has not yet reached its maximum potential. To overcome these problems, this research explores collaborative efforts in managing Ngliyep Beach marine tourism. This research aims to identify strategies that can maximize the attractiveness of beach tourism while analyzing the factors that hinder and support its development. Researchers use SWOT analysis, which is a method that highlights Strengths, Weaknesses, Opportunities and Threats. This approach empowers them to determine a combination of strategies that capitalize on Ngliyep Beach's strengths and take advantage of emerging opportunities, while mitigating weaknesses and addressing potential threats.